PENGEMBANGAN MEDIA PEMBELAJARAN IGNITION SYSTEM SEPEDA MOTOR PADA MATA KULIAH TEKNIK SEPEDA MOTOR - Muhammad Ekrima Said Buhohang; Buyung R. Machmoed; Muh. Yasser Arafat; Esta Larosa; Monica Pratiwi; Sugeng Pramudibyo (Universitas Negeri Gorontalo, 2023)
This research is motivated by the need for motorcycle ignition system learning media in motorcycle engineering courses, especially motorcycle ignition system material. This study develops learning media as learning aids according to the learning styles of Mechanical Engineering Education students who are more inclined to kinesthetic learning styles. The purpose of this study was to develop and test the feasibility of motorcycle ignition system learning media in motorcycle engineering courses. To develop and test the feasibility of the media, the method used in this research is Research Development, with a 4D model (define, design, develop, and disseminate). The development procedure begins with (1) describing the initial state, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product manufacturing (7) product validation, (8) revision product, (9) final product, (10) dissemination. Data collection techniques were carried out by means of observation, interviews, and questionnaires. This study produced motorcycle Ignition System learning media and the results of measuring the feasibility of the media with an average percentage value of design experts 89.15, material experts 90.76%, media experts 93.84, and user response 90.00%. The sum of the average scores of all grades is 90.18. The conclusion of the development of motorbike Ignition System learning media can be said to be very feasible to use.